MAURIAC SYNDROME WITH CELIAC DISEASE: RARE ASSOCIATION - Manish, Gutch; Singh, Saransh; Bhatacharya, Annesh; Singh, Harendra; Sukriti, Kumar; Sumit, Rungata (International Journal of Innovative Research in Medical Science, 2016)
Growth failure in type 1 Diabetes Mellitus can occur for several reasons. Mauriac syndrome is a rare cause of severe growth failure in type 1 Diabetes Mellitus.The classical severe presentation of Celiac Disease rarely occurs in type 1 Diabetes Mellitus patients, but more often patients have few/mild symptoms of Celiac Disease or are completely asymptomatic (silent CD). In fact diagnosis of Celiac Disease is regularly performed by means of the screening in type 1 Diabetes Mellitus patients.There may be different forms and etiologies involved in Mauriac syndrome. We hereby report a case of Mauriac syndrome in type 1 Diabetes Mellitus with simultaneous celiac disease which is very rarely reported.